Facilitating intercultural learning: Strategies and challenges in primary school virtual exchanges - Anisa, Rochmatika Nur; Sabilah, Fardini; Halimatussadiyah, Halimatussadiyah; Alam, Daniar Jauhar (Journal of English Language Teaching Innovations and Materials (Jeltim), 2025)
This study explores the challenges and strategies involved in facilitating virtual exchange programs for primary school students, a group often overlooked due to their beginner-level English proficiency. The shortage of English teachers in Indonesian primary schools further complicates participation in international collaborations. This research investigates how educators navigate these challenges, focusing on their pedagogical strategies, obstacles, and adaptations in virtual exchanges. Using a qualitative approach, the study gathers insights from an elementary school teacher in Indonesia responsible for international programs. Thematic analysis identifies three key strategies: L1 translation, authentic material integration, and structured preparation to enhance student engagement and comprehension. Despite these efforts, teachers face time constraints and difficulties in understanding discussion topics. Findings suggest that while L1 translation supports comprehension, excessive reliance may hinder English acquisition. The study emphasizes the need to balance linguistic and intercultural competencies through immersive, interactive learning. It advocates for inclusive educational practices that promote cross-cultural awareness and language development among young learners. Future research should explore diverse educational settings and scalable models for integrating virtual exchanges into primary English language teaching.